Phenotypic diversity and provenance variation of Cupressus funebris: a case study in the Sichuan Basin, China - Wang Yan; Yongqi Xiang; Mei Gao; Ruoyu Deng; Yan Sun; Renping Wan; Xianyi Pan; Wanzhen Li; Yu Zhong (PeerJ)
Background The species Cupressus funebris holds substantial ecological value and economic potential, particularly in the realms of rehabilitating barren mountain landscapes and advancing urban greening endeavors. However, inadequate attention has been given to research endeavors exploring the genetic diversity and morphological characteristics of Cupressus funebris, a deficiency that could potentially hinder its development, utilization, and conservation of genetic resources. Methods To rectify the shortage of existing basic morphological data, a morphological analysis was conducted in this study on 180 Cupressus funebris germplasm resources sourced from five provenances. Key traits explored included growth characteristics, overall morphology, branch/leaf features, and seed traits. This will facilitate the evaluation of genetic diversity in Cupressus funebris. Results The findings reveal a considerable level of phenotypic variation (PVC of 16.9%) and genetic diversity (1.97 index) in Cupressus funebris germplasm resources. The phenotypic differentiation is observed to be 48% between provenances and 52% within provenances, primarily attributed to variation originating from individual provenances. Based on these morphological characteristics, the germplasm resources have been categorized into four distinct groups: Ecological Restoration Planting, Secondary Reserve Forest, Urban Greening, and Timber Forest. Interestingly, the pattern of variation observed within these groups is irregular, exhibiting no significant correlation with their respective provenances. Furthermore, conifer trees sharing similar growth characteristics tend to display comparable patterns of random variation, suggesting potential underlying genetic mechanisms. This study significantly enriches the phenotypic dataset within the genetic variation research of Cupressus funebris, facilitating development and utilization for ecological construction, timber breeding, and horticultural greening.